Sedimentary Characteristics and Model of Estuary Dam-Type Shallow-Water Delta Front: A Case Study of the Qing 1 Member in the Daqingzijing Area, Songliao Basin, China - Huijian Wen; Weidong Xie; Chao Wang; Shengjuan Qian; Cheng Yuan (Applied Sciences)
The sedimentary characteristics and model of the shallow-water delta front are of great significance for the development of oil and gas reservoirs. At present, there are great differences in the understanding of the distribution patterns of estuary dams in the shallow-water delta front. Therefore, this paper reveals the distribution characteristics of estuary dams through the detailed dissection of the Qing 1 Member in the Daqingzijing area and establishes a completely new distribution pattern of estuary dams. By using geological data such as logging and core measurements, sedimentary microfacies at the shallow-water delta front are classified and logging facies identification charts for each sedimentary microfacies are developed. Based on the analysis of single-well and profile facies, the sedimentary evolution laws of the Qing 1 Member reservoirs are analyzed. On this basis, the sedimentary characteristics and model of the lacustrine shallow-water delta front are established. The results indicate that the Qing 1 Member in the Daqingzijing area exhibits a transitional sequence from a delta front to pro-delta facies and finally to deep lacustrine facies, with sediments continuously retrograding upward. Subaqueous distributary channels and estuary dams constitute the skeletal sand bodies of the retrogradational shallow-water delta. The estuary dam sand bodies are distributed on both sides of the subaqueous distributary channels, with sand body development gradually decreasing in scale from bottom to top. These bodies are intermittently distributed, overlapping, and laterally connected in plan view, challenging the conventional understanding that estuary dams only occur at the bifurcation points of underwater distributary channels. Establishing the sedimentary characteristics and model of the shallow-water delta front is of great significance for the exploration and development of reservoirs with similar sedimentary settings.